On the interaction of biological and mechanical factors in leaf vein formation. (November 2020) - Lin, S.; Chen, L.; Zhang, M.; Xie, Y.M.; Huang, X.D.; Zhou, S.W.
Highlights: Explaining the mechanism of leaf vein evolution. Exploring leaf vein evolution affected by leaf growing. Demonstrating the relationship between venation and leaf shape. Abstract: The stiffness and heat dissipation of thin planar structures in industrial engineering are taken as the background for this research. Plant leaves with various vein patterns, such as tobacco ( Nicotiana tabacum L. ) and chili ( Capsicum annuum L. ) leaves, are treated as the research objects. Through a combination of morphological and mechanical analysis, the distribution patterns and properties of leaf veins are mathematically characterized. A topological optimization algorithm is employed to simulate the vein growth process, thus revealing the effects of the mechanical and biological properties of different leaves on their vein morphologies. Additionally, the angles between the main and secondary veins are controlled to satisfy biological constraints. This comprehensive exploration of vein morphological formation can serve as a reference for the design of bionic thin planar structures in engineering.